User Satisfaction of the UBSI Online Exam System Based on End User Computing Satisfaction (EUCS) - Rakhmat Hadi Sucipto; Wahyu Indrarti; Rahayu Swastika; Helmy Ivan Taruna (Universitas Negeri Padang, 2025)
Universitas Bina Sarana Informatika (UBSI) implements an online exam system to evaluate learning during one semester and the end of the semester. However, the online exam system still raises weaknesses and shortcomings that are felt by users. Therefore, it is necessary to conduct research related to end-user satisfaction because this system is important for universities and user satisfaction is an important factor in the successful implementation of the online exam system. This study aims to analyze the level of user satisfaction of the online exam system of UBSI using the End User Computing Satisfaction (EUCS) method. The research involved 396 samples of UBSI active students who routinely use the online exam system. This study collected primary data by creating and distributing questionnaires through Google Forms. The collected data was analyzed with SmartPLS 4.0 software to test the validity, reliability, and hypothesis of the research. The results of the study show that there are three variables that have a significant effect on user satisfaction of the UBSI online exam system, namely 1) accuracy, 2) ease of use, and 3) timeliness. The other two, namely content and format, do not have a significant effect on user satisfaction of the online exam system. Based on the value of the determination coefficient, exogenous variables are able to influence endogenous variables by 59.8%. All independent variables were able to predict the results well because they had a Q-square (Q²) value of 0.577. The measure of effect (f²) of each independent variable that was proven to have a significant effect on user satisfaction of the online exam system was in the low category because the value was below 0.02.